Nuclear Magnetic Resonance Fingerprinting and Principal Component Analysis Strategies Lead to Anti-Tuberculosis Natural Product Discovery from Actinomycetes - Jianying Han; Xueting Liu; Lixin Zhang; Ronald J. Quinn; Miaomiao Liu (Antibiotics)
Background: The increasing prevalence of drug-resistant tuberculosis (TB) underscores the urgent need for novel antimicrobial agents. Methods: This study integrates cultivation optimization, nuclear magnetic resonance (NMR) fingerprinting, and principal component analysis (PCA) to explore microbial secondary metabolites as potential anti-TB agents. Results: Using the combined approach, 11 bioactive compounds were isolated and identified, all exhibiting anti-Mycobacterium bovis BCG activity. Notable findings include borrelidin, a potent threonyl-tRNA synthetase inhibitor with broad biological activities, and L-O-Lac-L-Val-D-O-Hiv-D-Val, a peptide isolated for the first time from a plant endophyte, demonstrating broad-spectrum antimicrobial activity. Additionally, elaiophylin and polycyclic tetramate macrolactams (PTMs) displayed significant bactericidal effects, with elaiophylin achieving complete BCG inhibition at 72 h and PTMs marking their first reported anti-TB activity. The study also identified bafilomycins as potent scaffolds for anti-TB drug development, showcasing rapid bactericidal activity at low MIC values. Conclusions: These findings emphasize the value of microbial metabolites as a reservoir of bioactive compounds and provide new avenues for developing next-generation anti-TB therapies.